PENGARUH CITRA MEREK, DESAIN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT - Nova Kurnia Dewi Lestari; Sri Ekowati (Yayasan Insani Mandiri Santani, 2020)
The objective of this study is to know the effect of Brand Image, Product Design and Price on the Purchasing Decision of Honda Beat motorcycles on students of the Faculty of Economics and Business, Muhammadiyah University of Bengkulu and to find out which factors are the most dominant affect the purchasing decisions of Honda beat motorcycles. The type of study is survey research methods with quantitative data analysis. In this study the data obtained through observation, literature study and questionnaires that have been distributed to 96 respondents of the Faculty of Economics and Business, Muhammadiyah University of Bengkulu using the probability sampling method. The results of this study show that the result of multiple linear regression test using the SPSS program is Y = 8,347+ 0.367 (X1) + 0.234 (X2) + 0.454 (X3). The results of the coefficient of determination (R2) Adjusted R Square value is 0.522 or 52.2%, where the coefficient of determination means that both the brand image (X1), product design (X2) and price (X3) contributed 52.2 % in affecting the purchasing decisions (Y) for Honda Beat motorcycles. Hypothesis testing by t test shows that the brand image variable (X1) is 0.004 <0.050, the product design variable (X2) is 0.007 <0.050 and the price variable (X3) is 0.000 <0.050 which means that all variables have a partial effect on purchasing decisions, and F test shows that the brand image variable (X1), product design (X2), and price (X3) affect the purchasing decision (Y) with a significance level <0.050. This means Ho is rejected, and Ha is accepted